Reduction in post‐operative pancreatic fistula with polyethylene glycol and recombinant human albumin sealant following stapled distal pancreatectomy. Issue 11 (13th September 2021) - Privett, Benjamin J.; Perini, Marcos V.; Weinberg, Laurence; Fink, Michael A.; Muralidharan, Vijayaragavan; Lee, Eunice; Starkey, Graham; Jones, Robert; Lin, Yi‐Ju; Nikfarjam, Mehrdad
Abstract: Background: Postoperative pancreatic fistula (POPF) remains a significant cause of morbidity in patients undergoing distal pancreatectomy (DP). The use of polyethylene glycol (PEG) and recombinant human albumin sealant gel applied to the transected pancreatic margin in DP may reduce POPF rates and was assessed. Methods: A retrospective single centre cohort study of patient undergoing DP at an Australian high volume tertiary institution between January 2015 and January 2021. Rates of POPF in patients undergoing stapled pancreatic transection with PEG sealant were compared to other methods. Results: A total of 54 cases were identified for analysis, with 16 undergoing stapled DP combined with staple line application of PEG (PEG group). Most patients in the control group had stapled DP 92% (35 of 38), with 47% (18 of 38) combined with a reinforcing buttress, with or without the use other glue types. Overall, 28 of 54 (52%) developed a POPF, with a significantly lower rate in the PEG group (3 of 16 vs. 25 of 38 in the Control group; p = 0.003). Clinically significant Grade B/C POPF was lower in the PEG group (0 of 16 vs. 9 of 28 in the Control group; p = 0.045), and patients in the PEG group had a shorter median (range) length of hospital stay (6 [4–14] days vs. 10 [6–41] days p = 0.04). Conclusion: Stapled DP with the application of PEG and recombinant human albumin sealant to the transection line appears to be associated with a lower rate of clinically significant POPF. Abstract : Stapled pancreatic resection before and after PEG and recombinant human albumin sealant application